(untitled) (British Journal of Global Ecology and Sustainable Development, 2022)
Dear reader, in this article we have been given information about the structure of the membrane of epithelial tissue and the classification of glands , types of cell deposition and so on . The information of the article is taken from some at the international level We tried to summarize and give information using different sites and whales.